Impact on patients of the coronovirus disease 2019 pandemic and postponement of cochlear implant surgery: a qualitative study. Issue 10 (18th October 2021) - Abrar, R; Bruce, I A; O'Driscoll, M; Freeman, S; de Estibariz, U Martinez; Stapleton, E
Abstract: Objective: This study aimed to explore the impact of the coronavirus disease 2019 pandemic and postponement of elective surgical procedures for profoundly deaf patients awaiting cochlear implantation. Method: Open-ended questionnaires were sent to all adult patients awaiting cochlear implantation surgery. Qualitative analysis was performed using a grounded theory approach. Results: Participants described a primarily negative impact on wellbeing from the surgery delay, expressing feelings of isolation or loneliness. Low mood, depression or hopelessness were commonly expressed by elderly participants; frustration and anxiety were described by young adults. Participants described a negative impact on their general daily life, describing difficulties communicating with facemasks and struggles with reliance on telephone communication because of social distancing. Despite these significant psychosocial challenges, only a minority described adaptive coping strategies. Discussion: Profoundly deaf patients may be at greater psychosocial risk because of unique challenges from their hearing disability. Our findings can be used to develop evidence-driven strategies to improve communication, wellbeing and quality of life.